A Metallogenic Model for Bauxite Deposits and Geophysical Prospecting Methods: Using the Sedimentary Type in Northern China as an Example - Guoqiang, Xue; Nannan, Zhou; Wenbo, Guo; Shun, Zhang (Frontiers in Earth Science, 2022)
An ideal metallogenic and prospecting model has important guiding significance for aluminum ore development and geophysical exploration. Previous research in this field only focused on ore body evaluations and metallogenic belts. Selection of reasonable geophysical methods for exploration of bauxite deposits is still challenging. To solve these problems, a new metallogenic model based on the new geological information is established firstly. The ore-bearing rock and ore bodies of sedimentary bauxite deposits are strictly controlled by the paleo-topographic conditions. The undulating shapes of the paleo-topography control the scales and shapes of ore-bearing rock series and bauxite ore bodies. Then, different geophysical methods applied for exploration of bauxite deposit are analyzed based on the petrophysical measurement. For the areas with thick overburden and large buried depths, it was found that fixed-loop transient electromagnetic (TEM), high-precision gravity, and seismic exploration methods were most effective. In regard to the areas with thin overburden and small buried depths, direct current (DC) sounding, high-precision gravity, seismic exploration, and TEM methods were considered to be effective. However, for the areas with very shallow buried depths, DC sounding and seismic exploration methods were deemed to be more suitable. This study selected the actual exploration processes of the Wanggudong bauxite mining area in western Henan as an example, and the application of a DC sounding method for sedimentary-type bauxite was successfully introduced.